Pemakaian Hanfu dalam Konten Digital Remaja Selama Masa Pandemi - Ramadarti, Nur; Rudiansyah, Rudiansyah (Pascasarjana, Universitas Negeri Gorontalo, 2021)
Hanfu is a traditional Chinese cloth that is very famous for its beauty and uniqueness. A strong characteristic makes Hanfu able to attract the attention of anyone who sees it, especially young people. Some searches on social media for young people found many young people who use Hanfu as the main costume in the content they publish. This is the background for the author to examine how attractive the role of Hanfu in digital content for young people is during this pandemic. In this research, the writer uses the descriptive analysis method. The results of the study using descriptive analysis among students and young people who like Chinese culture, 80% think that the use of Hanfu in content during this pandemic is very interesting, because it is considered unique and different from others, and teaches about cultural values from the Chinese nation. In addition, the use of Hanfu in youth content is considered to be able to increase knowledge about Chinese culture, especially for students majoring in Chinese Literature.Keywords: Hanfu; Youth Digital Contents; Pandemic